#DeathToFreedomOfSpeech - Dominik Stosik (Ksiegarnia Akademicka Publishing, 2019)
In this analysis the author sets out to examine the concept of freedom of speech on the internet, drawing upon the development of the World Wide Web, the Big-Data-Trade-Off-Dilemma and the nothing-to-hide argument fallacy. A key finding is the observation of a multitude of emerging challenges in the field of ethics, privacy, law and security. Furthermore the most recent exertion of influence on the freedom of speech, that is to say astroturfing should adduce as an instance to demonstrate the possibilities of manipulating public opinion. Further on, the analysis of governmental military enhancement programmes and the example of a recent entertainment programme production shall serve as a visualisation that the research on unprecedented signal resolution and datatransfer bandwidth between the brain and electronics might be far more close to reality than one might be expecting. The results suggest that the freedom of speech is preceded by the freedom of thinking. Its manipulation on a bigger scale (e.g. national elections) could serve as a new way of psychological warfare and therefore the freedom of thinking, or the right to a free mind should remain unviolated.